Immunohistochemical features of actinic keratosis. - Oshivalova, O. O.; Kaluzhna, L. D.; Shponka, I. S.; Poslavska, O. V. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. Skin damage by type of actinic keratosis (AK) and squamous cell carcinoma in situ (SCCis) are considered to be precursors to cSCC. A common theory about the gradual transition from normal skin to AK and cSCC. Some scientists believe that AK is the same cancer as cSCC. Objective. To investigate the complex of histological, immunohistochemical characteristics of observations of areas of AK, SCCis and cSCC with the purpose of further improvement of preventive measures. Methods. Bioassays of 20 (50%) patients with AK were used, 10 (25%) were SCCis, and 10 (25%) were CCSCs. The levels of epidermal dysplasia (KIN) have been determined. Light microscopy was performed with a Zeiss Primo Star light microscope using × 10, × 20, × 40 lenses, and a morphometric examination was performed using a Zeiss Primo Star microscope camera - Axiocam ERC 5s with ZEN 2 blue edition licensed software. Statistical processing of the material was performed using Microsoft Office Exel software. Results. When comparing the expression levels of the investigated markers in the AK foci, the "cancer field" and the SCC, a significant difference occurred only in the expression level of pcna (p = 0.014 and p = 0.011). With the increase in the level of dysplasia of the epidermis there is a tendency to increase the level of bcl-2 (R2 = 0.815), p53 (R2 = 0.744) vegf mean (R2 = 0.680). Trends in increasing pcna and vegf levels against the background of decreasing levels of bcl-2, p53, and p27 in the SCC zone (R2 = 1.0). Conclusion. The study confirms the scientific opinion about the closeness of immunohistochemical changes in the focus of AK and cSCC.